THE EFFECTIVENESS OF ONLINE ACL INJURY PREVENTION EDUCATION FOR SPORTS COACHES. Issue 4 (28th April 2020) - Russomano, James; Ologhobo, Titilayo; Janosky, Joseph J.; Goldsmith, Sandra; Marx, Robert G.; Kinderknecht, James; Robbins, Laura
Background: The efficacy of ACL injury prevention programs (IPP) have been well-defined by sports medicine researchers over the past decade, but the adoption and implementation of effective ACL IPP is noticeably deficient in real-world situations. One barrier to the widespread implementation of ACL IPP by sports coaches is the limited understanding of how to effectively deliver these programs to young athletes. The ability to effectively identify and correct high-risk movements during the performance of neuromuscular training and athletic activities has been reported as a key factor in the effectiveness of an ACL IPP. Educational opportunities to train sports coaches to effectively deliver ACL IPP programs are not common, but those that do exist are often delivered in live settings. Live educational workshops are resource-intensive and limit the number of participants that can be trained over time. Educational workshops offered online can deliver information efficiently to large numbers of individuals but have not yet demonstrated education outcomes that are equivalent to live education events. Hypothesis/Purpose: The purpose of this study is to investigate the association between participation in an online educational workshop for coaches and knowledge of how to effectively employ an ACL IPP with young athletes. We hypothesize that participation in an online educational workshop is associated with increased knowledge of how to effectively employ an ACL IPP with young athletes and high levels of program satisfaction. Methods: An online educational workshop was developed to teach sports coaches how to effectively employ an ACL IPP program with young athletes. Coaches from throughout the United States were recruited to access the workshop through a computer-based learning management system. A series of instructional videos were used to deliver educational content to participants. Pre- and post-workshop surveys were utilized to determine program effectiveness and participant satisfaction. Results: 468 coaches (77% male) participated in the pilot phase of the program. Nearly two-thirds of all participants demonstrated an increase in knowledge immediately post-intervention. Mean knowledge scores increased by 33% (56.5 to 74.9, p < 0.001). 89% of participants rated the workshop favorably and 90% of participants reported that they would recommend the workshop to other coaches. Conclusion: Results indicate that an online workshop for sports coaches improved the knowledge needed to effectively deliver an ACL IPP to young athletes. These findings support the continued evaluation of computer-based learning management systems to deliver online ACL IPP workshops to sports coaches. Table 1. Sports coached by respondents Sports N % Basketball 127 29% Soccer 115 26% Football 97 22% Softball 56 13% Other 53 12% Track and field 49 11% Baseball 48 11% Volleyball 44 10% Cross country 33 8% Tennis 24 5% Lacrosse 18 4% Cheerleading 18 4% Table 2. Coaches who answered each knowledge question correctly Question Pre N Pre % Post N Post % Change p When assessing your athlete's posture, which parts of the body should be aligned with the hip to demonstrate proper posture? 132 28.2% 281 60.0% 112.9% 0.001 During your team's warm-up, you notice an athlete whose hips are sagging while performing a plank. Which of the following is an appropriate cue to correct their technique? 227 48.5% 290 62.0% 27.8% 0.001 Maintaining proper alignment of the hip, knee, and ankle is critical in many sports. What happens when an athlete's knee rotates inward? 414 88.5% 431 92.1% 4.1% 0.05 Which of the following coaching cues is most appropriate when teaching an athlete to absorb forces when landing from a jump? 284 60.7% 400 85.5% 40.8% 0.001 Table 3. Level of agreement on Satisfaction Statement Strongly Agree Agree Neutral Disagree Strongly Disagree I am satisfied with this workshop 51.1% 38.0% 7.7% 1.1% 2.1% I would recommend this workshop to other coaches 54.9% 34.8% 7.1% 1.1% 2.1%